A possible role of vitamin D receptors in regulating vitamin D activation in the kidney. - Iida, K (1995)
The vitamin D endocrine system is regulated reciprocally by renal 25-hydroxyvitamin D3 1 alpha- and 24-hydroxylases. Previously, we reported that renal proximal convoluted tubules, the major site of 1 alpha, 25-dihydroxyvitamin D3 production, have vitamin D receptors. In the presence of vitamin D receptors, renal proximal convoluted tubules cannot maintain the state of enhanced production of 1 alpha, 25-dihydroxyvitamin D3. To clarify this discrepancy, we proposed a working hypothesis for the reciprocal control of renal 25-hydroxyvitamin D3 1 alpha- and 24-hydroxylase activities. In rat models of enhanced renal production of 1 alpha, 25-dihydroxyvitamin D3, expression of vitamin D receptors and 25-hydroxyvitamin D3 24-hydroxylase mRNAs was strikingly suppressed in renal proximal convoluted tubules but not in the cortical collecting ducts. In vitamin D-deficient rats with up-regulated renal 25-hydroxyvitamin D3 1 alpha-hydroxylase activity, expression of vitamin D receptor mRNA in renal proximal convoluted tubules was also down-regulated, indicating that the down-regulation of vitamin D receptor mRNA is not the result of the enhanced production of 1 alpha, 25-dihydroxyvitamin D3. In Japanese quail models with up-regulated renal 25-hydroxyvitamin D3 1 alpha-hydroxylase activity by sex steroids, expression of vitamin D receptor mRNA was also down-regulated in the kidney but not in the duodenum. These results suggest that the down-regulation of vitamin D receptors plays a critical role in production of 1 alpha, 25-dihydroxyvitamin D3 in renal proximal convoluted tubules.